Combination of Sonogashira coupling and 5-endo-dig cyclization for the synthesis of 2, 6-disubstituted-5-azaindoles. Issue 3 (1st February 2019) - Balfour, Michael N.; Zukerman-Schpector, Julio; Rodriguez, Maria José Dávila; Reis, Joel Savi; Esteves, Carlos Henrique A.; Stefani, Hélio A.
Abstract: The synthesis of a library of 2, 6-disubstituted-azaindoles relying on Sonogashira cross-coupling and intramolecular cyclization is described. Eleven examples of 6-alkynyl derivatives and three examples of 3-bromo-5-azaindoles are reported. One of the 3-bromo-5-azaindoles was also further functionalized with two different aryl trifluoroborate salts via Suzuki-Miyaura coupling reaction. Graphical Abstract: